A Novel Method for UHF RFID Tag Tracking Based on Acceleration Data - Parr, Andreas; Miesen, Robert; Kirsch, Fabian; Vossiek, Martin (6th Annual IEEE International Conference on RFID (IEEE RFID 2012), 2012)
Options for RFID tag tracking and localization are an essential asset for future high performance RFID reader systems. A reader with long reading range, high reading rate and multi-tag capability should be able to assist the user to find / retrieve tags, to create spatial object maps and to restrict the reading range to specific regions of interest. In this paper we introduce a novel method for RFID tag tracking with a moving for example handheld reader. An inertial measurement unit (IMU) is used to characterize the handheld trajectory. Contrary to approaches where IMU locations are reconstructed via double integration of the acceleration data, our novel technique only uses acceleration data without knowledge of the actual antenna locations. Inexpensive, standard inertial sensors can be used in this approach, and the usual drift and offset issues associated with IMU-based positioning are avoided. Parallel to the IMU acceleration data, the phase of the backscattered RFID signal is input. Double differentiation of the signal phase yields a second acceleration data set. By comparing the IMU and the RFID signal phase acceleration data, the direction of arrival of the RFID signal is estimated using a quasi-spatial optimal filter. This paper introduces the novel RFID tracking approach and illustrates its capability with numerical simulations and experimental results. This novel approach is a simple, yet promising, solution which can be implemented in any handheld reader and will improve its functionality considerably. © 2012 IEE
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.anovel_8
Keywords: angle of arrival; phase measurement; UHF RFID